Black and white : from snapshots to great shots - Batdorff, John (Peachpit Press, 2012)
"For photographers interested in black and white, this video by pro photographer John Batdorff will help you conquer the fundamentals and capture stunning pictures. In this stunning, high-quality streaming video, Batdorff starts with the basics--composition, light, contrast, and textures--and when to choose black and white. He covers all the key camera features that affect your image (regardless of what type of DSLR you have), including the shutter speed's ability to freeze and convey motion, as well as aperture's direct correlation with depth of field. Once you've captured those shots, John takes you step-by-step through color conversion and post-processing in Lightroom. He also covers the cool enhancements that can be added with Nik Software Silver Efex Pro. This video is for beginning-to-intermediate digital photographers to understand the basics and bring their own unique artistic expression to any situation whether taking portraits, action shots, landscapes, studio, or lifestyle shots."--Resource description page.